Development of a barometer to display and monitor health and wellbeing on the neighborhood level. (13th November 2019) - Hilger-Kolb, J; Röhrbein, H; Kairies, H; Heinrich, K; Hoffmann, K
Abstract: Background: Neighborhoods and their characteristics play a key role for establishing and maintaining health and wellbeing of their residents. However, before programs promoting health and wellbeing in the neighborhood can be planned and implemented, it is necessary to identify local needs for action. This is especially important for the stakeholders that work in the neighborhood (e.g., employees of the local community, headmasters of schools). We thus developed exemplary for Herzogenried -a neighborhood in the German city of Mannheim- a barometer that aims to assess and monitor health and wellbeing in the neighborhood and indicates potential needs for action. Methods: We conducted a detailed literature search to identify indicators that were associated with health and wellbeing in neighborhoods. Based on the search we created a primary list of indicators, which we presented and discussed during 15 meetings with a total of 26 different stakeholders. Available data on the indicators agreed on were checked for accuracy, statistically processed, and visualized for incorporation into the barometer. Results: The barometer consists of the following eight dimensions which in total include 80 indicators: population structure, population development, household structure, material wellbeing, education, family and upbringing, health, and personal security. The barometer also includes a map that displays structural characteristics of the neighborhood such as physicians, schools, supermarkets. An important challenge we faced was the availability of indicators as some of them were only accessible at the community level or for specific age groups. Conclusions: The barometer offers a comprehensive overview on the neighborhood, provides first hints for the local stakeholders on needs for action, and helps to prioritize the issues that should be addressed to promote health and wellbeing in Herzogenried. It will also serve as a prototype for other neighborhoods in the future. Key messages: The barometer was planned to serve as a transferable tool to identify and prioritize action steps for neighborhood development and to help promoting health and wellbeing of their residents. As the barometer displays indicators relevant for various community stakeholders it can serve to identify joint goals and thus foster stronger trans-sectoral collaboration at the neighborhood level.